Trematodes of dairy cattle grazing in Cajamarca: Fasciola hepatica and Calicophoron microbothrioides - Torrel, Severino (2023)
The study determines the prevalence of trematodes through coproparasitology in grazing dairy cattle in six districts of the Cajamarca region. The analyzes and processing of the faecal samples were carried out by natural sedimentation. The proportion of parasitized animals was 50.4 ± 2.1% (1092/2169), only Fasciola hepatica 32.4 ± 2.0% (703/2169), Calicophoron microbothrioides 17.9 ± 1.6% (389/2169) and coinfection by both parasites was 7.51 ± 1.11% (163/2169). The prevalence by district in Cajamarca was 49.5±5.0% (188/380), Baños del Inca 61.2±5.6% (181/296), La Encañada 80.7±4.1% (284/352), Celendín 45.4±5.0% (171 /377), San Juan 50.0±5.0% (190/380) and Chota 20.3±4.0% (78/384). There was no statistical association in the presence of both trematodes in the animals (p>0.95), nor was a correlation found between the altitude of each district and the presence of faecal eggs (r=0.19). It is concluded that the prevalence of trematodes in extensively reared dairy cattle in Cajamarca is high, with the greatest presence of F. hepatica, followed by C. microbothrioides and their coexistence.